2003
DOI: 10.1074/jbc.m305722200
|View full text |Cite
|
Sign up to set email alerts
|

ATP Potentiates Interleukin-1β-induced MMP-9 Expression in Mesangial Cells via Recruitment of the ELAV Protein HuR

Abstract: Renal mesangial cells express high levels of matrix metalloproteinase 9 (MMP-9) in response to inflammatory cytokines such as interleukin (IL)-1␤. We demonstrate here that the stable ATP analog adenosine 5-O-(thiotriphosphate) (ATP␥S) potently amplifies the cytokine-induced gelatinolytic content of mesangial cells mainly by an increase in the MMP-9 steady-state mRNA level. A Luciferase reporter gene containing 1.3 kb of the MMP-9 5-promoter region showed weak responses to ATP␥S but confered a strong ATP-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 53 publications
(77 reference statements)
1
56
1
2
Order By: Relevance
“…Simultaneously, some inflammatory cytokines, most importantly IL-1, IL-6, and TNFα, can strongly up-regulate matrix metalloproteinase 9 (MMP-9) [19][20][21][22] , an independent biochemical predictor of HT in all stroke subtypes [23] . A previous study indicated that MMP-9 is involved in tPAassociated hemorrhage, and combination therapy of tPA with MMP inhibitors may help decrease the risk and severity of HT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, some inflammatory cytokines, most importantly IL-1, IL-6, and TNFα, can strongly up-regulate matrix metalloproteinase 9 (MMP-9) [19][20][21][22] , an independent biochemical predictor of HT in all stroke subtypes [23] . A previous study indicated that MMP-9 is involved in tPAassociated hemorrhage, and combination therapy of tPA with MMP inhibitors may help decrease the risk and severity of HT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the contradictory effects of rapamycin on MMP-9 mRNA levels and MMP-9 promoter activity, we postulated that the negative effects on MMP-9 by rapamycin may result from additional posttranscriptional events. Notably, we previously could demonstrate that several copies of destabilizing AU-rich elements (AREs) present in the 3´-UTR of rat MMP-9 gene are critically involved in the posttranscriptional regulation of MMP-9 [15,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the data of the present study, this suggests that the RNA stabilization and nuclear export function of HuR can be separated from each other, depending on the RNA target sequence. According to this, the stabilization of mRNAs depends on the interaction of HuR with an ARE sequence and occurs in the cytoplasm (61,93,94). In contrast, the binding of HuR to the CD83 PRE does not affect the decay of transcripts bearing this RNA sequence.…”
Section: Discussionmentioning
confidence: 99%